2017
DOI: 10.1186/s13065-017-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of the new 1,3-dimethylxanthine derivatives with thiazolidine-4-one scaffold

Abstract: BackgroundThe xanthine structure has proved to be an important scaffold in the process of developing a wide variety of biologically active molecules such as bronchodilator, hypoglycemiant, anticancer and anti-inflammatory agents. It is known that hyperglycemia generates reactive oxygen species which are involved in the progression of diabetes mellitus and its complications. Therefore, the development of new compounds with antioxidant activity could be an important therapeutic strategy against this metabolic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This has helped in exploring the significance of these derivatives in various therapeutics applications such as adenosine receptor antagonists, inducers of histone deacetylase activity, antitumor drugs, anti asthmatic drug, psycho-stimulant drug etc [ 10 , 11 , 12 , 13 , 14 ]. The wider pharmaceutical applications of natural xanthine derivatives has prompted medicinal chemist or pharmaceutical companies to go for certain changes over lead molecule to develop more specific compounds using synthesis methodologies [ 15 , 16 , 17 , 18 , 19 ]. In drug development process, one of the major challenges is deciding the lead molecule which would act as a scaffold to provide avenue for achieving molecular diversity.…”
Section: Introductionmentioning
confidence: 99%
“…This has helped in exploring the significance of these derivatives in various therapeutics applications such as adenosine receptor antagonists, inducers of histone deacetylase activity, antitumor drugs, anti asthmatic drug, psycho-stimulant drug etc [ 10 , 11 , 12 , 13 , 14 ]. The wider pharmaceutical applications of natural xanthine derivatives has prompted medicinal chemist or pharmaceutical companies to go for certain changes over lead molecule to develop more specific compounds using synthesis methodologies [ 15 , 16 , 17 , 18 , 19 ]. In drug development process, one of the major challenges is deciding the lead molecule which would act as a scaffold to provide avenue for achieving molecular diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of new xanthine derivatives with thiazolidine-4-one scaffold (6a–k) ( Figure 1 ) were presented in our previous paper [ 38 ]. Some of these compounds showed good antioxidant effects in terms of the antiradical scavenging effect (DPPH, ABTS) and phosphomolybdenum reducing antioxidant power [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…ACS reagent), dimethyl sulfoxide (DMSO, p.a., ACS regent), Mueller–Hinton agar medium (Oxoid), Sabouraud agar medium were purchased from Sigma Aldrich. Xanthine derivatives with thiazolidine-4-one scaffold (XTDs: 6c, 6e, 6f, 6k) have been synthesized by our research group and were reported in a previous paper [ 38 ]. Bacterial strains ( Staphyloccoccus aureus ATCC 25923, Sarcina lutea ATCC 9341, Escherichia coli ATCC 25922) and yeast strains ( Candida albicans ATCC 10231, Candida glabrata ATCC MYA 2950, Candida parapsilosis ATCC 22019) were obtained from the Department of Microbiology, “Grigore T. Popa” University of Medicine and Pharmacy, Iasi, Romania.…”
Section: Methodsmentioning
confidence: 99%
“…Constantin et al [147] developed a novel, selective, nontoxic synthesis of thiazolidine-4-one derivatives containing a xanthine structure and evaluated them for antioxidant and antidiabetic activity. Initially, theophylline (1,3-dimethylxanthine) reacted with sodium methoxide and furnished the salt, which combined with ethyl chloroacetate and gave theophylline ethyl acetate.…”
Section: Antioxidant Activitymentioning
confidence: 99%